Resiliency: A Systematic Review of Adult Characterological Measures of Resilience and Reliability and Validity Generalization Studies of the Brief Resilience Scale - Allan, Teresa A. (Université d'Ottawa / University of Ottawa, 2021)
This dissertation consists of two projects. Project 1 is comprised of two systematic review studies in which self-report measures of adult characterological resilience were identified and summarized. In Study 1, 51 personality-based instruments across five personality-based resilience constructs (ego-strength, grit, hardiness, mental toughness, and resilience) were identified. Information for each measure inclusive of measure title, construct, item count, factors, response scale and items, scoring method, and score range was summarized. In Study 2, 1,322 articles were identified that described 1,193 studies and 1,351 participant samples who completed between one and four of these resilience measures. Measure use frequency and contextual use information related to study and sample attributes are summarized. Project 2 is a series of meta-analyses that were conducted to investigate the psychometric properties of scores on the Brief Resilience Scale (BRS) reported in 149 studies of adult participants. Reliability generalization methods are used to summarize 86 observations of internal consistency (mean Cronbach’s α = .86) and validity generalization methods are used to summarize eight observations of convergent validity (Mr = .61). Concurrent validity is also investigated via validity generalization methods for the most frequently observed mental health correlates of BRS scores. For each set of mental health measures, an estimated summary effect was calculated (anxiety, Mr = -.47; depression, Mr = -.49; optimism, Mr = .44; social support, Mr = .24; and stress, Mr = -.53). Of the significant moderators conducted for concurrent validity estimates, the largest was sample category (accounting for 100% of the variance in the observed correlations between the BRS and measures of social support). Geographic location and participant age, accounted for 55%, and 24%, of the variation in the observed correlations between the BRS and significantly moderated the relation between the BRS and perceived stress. Discussion for both projects include how the obtained relate to resilience theory, and the potential broader implications of these findings. Also based upon these reviews and meta-analyses, the challenges of resilience measure use are discussed and observations/recommendations are provided.
Keywords: Resilience; Hardiness; Ego-Strength; Mental Toughness; Grit; Brief Resilience Scale; BRS